2017
DOI: 10.1021/acsphotonics.7b00953
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Quenching in Nanoantenna–Emitter Systems Enabled by External Detuned Cavities: A Path to Enhance Strong-Coupling

Abstract: We show that a broadband Fabry-Perot microcavity can assist an emitter coupled to an off-resonant plasmonic nanoantenna to inhibit the nonradiative channels that affect the quenching of fluorescence. We identify the interference mechanism that creates the necessary enhanced couplings and bandwidth narrowing of the hybrid resonance and show that it can assist entering into the strong coupling regime. Our results provide new possibilities for improving the efficiency of solid-state emitters and accessing diverse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 52 publications
5
95
0
Order By: Relevance
“…In that case, the system is expected to behave more "classically" so that low-order cumulant expansions could provide a better approximation than in the cases studied here, in particular under driving by external coherent laser pulses. Furthermore, the capability of the method to treat an arbitrary spectral density could be exploited to study emitter dynamics in systems that are not well-described by a single or few cavity modes, such as found in complex nanoplasmonic or hybrid plasmonic-dielectric structures [10][11][12][13]42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, the system is expected to behave more "classically" so that low-order cumulant expansions could provide a better approximation than in the cases studied here, in particular under driving by external coherent laser pulses. Furthermore, the capability of the method to treat an arbitrary spectral density could be exploited to study emitter dynamics in systems that are not well-described by a single or few cavity modes, such as found in complex nanoplasmonic or hybrid plasmonic-dielectric structures [10][11][12][13]42 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, it has been shown that strong light-matter coupling can be achieved using a large variety of physical implementations as the "cavity" that provides the electromagnetic field confinement. These include Fabry-Perot cavities consisting of two mirrors 5 , propagating surface plasmon polaritons 6 , plasmonic hole 7 and nanoparticle arrays 8 , isolated plasmonic nanoparticles 9 and nanoparticle-on-mirror geometries 10,11 , as well as hybrid cavities combining plasmonic and dielectric materials [12][13][14] . In many of these systems, the electromagnetic field modes are not well-described by isolated lossy cavity modes, and a correct treatment demands theoretical approaches that are able to deal with the complexity of the electromagnetic field modes and their spectrum.…”
mentioning
confidence: 99%
“…Coupling between microcavities and plasmonic lattices at infrared frequencies has also been previously shown 34 . In addition, hybrid systems consisting of plasmonic particles and quantum emitters embedded in microcavities have been studied theoretically 35,36 . Here, we realize similar concepts experimentally by incorporating monolayer WS2 and plasmonic nanoparticle arrays into a common microcavity system.…”
Section: The Concept Of Oscillator Strength Borrowing Let Us Considementioning
confidence: 99%
“…The freedom of structural design will allow optimal integration of surface-plasmonic nanostructures into dielectric microcavities, whereas the coupling between the plasmonic and optical modes leads to a combination of high Q-factor and nanoscale mode volume, further enhancing the light-matter interaction of single emitters coupled to such hybrid modes. [172][173][174] It is highly expected that the spatial and spectral tunability could enable the most optimized emitter-cavity matching, resulting in even higher single-photon extraction efficiency than the micropillarbased cavities, [18,138,139] a crucial need for photon-based quantum computing processes such as the boson sampling. [175,176] By entering the strong coupling regime with tunable cooperativity, photon trains of on-demand quantum bunching could be realized.…”
Section: Discussionmentioning
confidence: 99%